Analisis Framing Pemberitaan Ferdy Sambo Divonis Hukuman Mati Pada Media CNNIndonesia.com Dan Tempo.co Periode Tanggal 13 Februari -16 Februari 2023 - Reky Arya Andriansyah (Student Scientific Creativity Journal, 2023)
Senior police officer Ferdy Sambo is involved in a premeditated murder case against his adjutant. This is national news which is reported in various media because it has a strong influence, including the media CNNIndonesia.com and Tempo.co. The method used is descriptive qualitative research with the Constructivism paradigm for Framing Analysis theory. Robert N. Entman is the subject of this research. See both media in Framing the construction of media reality. In reporting on Ferdy Sambo who was sentenced to death for reporting from 13 February to 16 February 2023. The results obtained are, there are differences in Framing. Media CNNIndonesia.com contains news based on the factual point of view of the source and there is an analogical title. Meanwhile, Media Tempo.co-publishes news based on facts and emphasizes news content as reinforcement and adds Ferdy Sambo to each news title to make it easier for readers.